Best Answer

Let's explain with an example: 2x - 7y = 11 5x + 7y = 3 To solve this system of equations by elimination we "add" the second equation to the first equation. So basically: 2x + 5x - 7y + 7y = 11 + 3 Which then symplifies to: 7x = 14 and x = 2 Then plug x = 2 into the original equation: 5(2) + 7y = 3 Which leads to: y = -1 So the solution is (2,-1).

Q: How do you use the elimination method using x and y?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Given: 2y = x + 2 x - 3y = -5 ∴ y = x/2 + 1 ∴ x - 3(x/2 + 1) = -5 ∴ x - 3x/2 - 1 = - 5 ∴ -x/2 = -4 ∴ x = 2 ∴ 2y = 2 + 2 ∴ y = 2 ∴ {x, y} = {2, 2}

9x-6y-(12*2y)=0 9x-6y-24y=0 9x-30y=o 9x=30y 3x=10y y=0.3x x=10/3y

4x-2y = 6 -7x+2y = -15 Add both equations together in order to eliminate y: -3x = -9 Divide both sides by -3 in order to find the value of x: x = 3 Substitute the value of x into the original equations to find the value of y: Solution: x = 3 and y = 3

Use the substitution method to solve the system of equations. Enter your answer as an ordered pair.y = 2x + 5 x = 1

You solve this by theoretically diverting the hypotenuse of the x divided by the overall beneficial procedure of y

Related questions

Using the elimination method, 3x + (2y) times 18x - 3y - 5 gives the result of 36xy + 3x - 3y - 5.

By elimination: x = 3 and y = 0

x-9y

Do you mean: x+y = -1 and 4x+y = -10 If so then: x = -3 and y = 2

Yes and it works out that x = 3 and y = 4

16

Solving by the elimination method gives: x = 3 and y = 2

Convert the following using the step method hint use your worksheets

x+y=2 x-4=4

A={x/x is factor of 12

Solving by the elimination method: x = 7 and y = 2

X=0 and y=0